Made in Newark : Cultivating Industrial Arts and Civic Identity in the Progressive Era - Shales, Ezra (Book collections on Project MUSE., 2010)
Made in Newark describes a changing industrial city at the dawn of the twentieth century, when the city's outspoken library director, John Cotton Dana, collaborated with industrialists, social workers, and New Women to reconfigure a cultural institution for a city in flux. This is the story of experimental library exhibitions and the founding of the Newark Museum Association-a project in which cultural literacy was intertwined with lessons in civics and consumption. It explores precedents for contemporary debates over the ways the library and museum engage communities, define heritage.